Neutrino Telescopes and High-Energy Cosmic Neutrinos - Andrea Palladino; Maurizio Spurio; Francesco Vissani (Universe, 2020)
In this review paper, we present the main aspects of high-energy cosmic neutrino astrophysics. We begin by describing the generic expectations for cosmic neutrinos, including the effects of propagation from their sources to the detectors. Then we introduce the operating principles of current neutrino telescopes, and examine the main features (topologies) of the observable events. After a discussion of the main background processes, due to the concomitant presence of secondary particles produced in the terrestrial atmosphere by cosmic rays, we summarize the current status of the observations with astrophysical relevance that have been greatly contributed by IceCube detector. Then, we examine various interpretations of these findings, trying to assess the best candidate sources of cosmic neutrinos. We conclude with a brief perspective on how the field could evolve within a few years.